Recurrent Germline DLST Mutations in Individuals with Multiple Pheochromocytomas and Paragangliomas - Remacha, Laura; Pirman, David; Mahoney, Christopher E.; Coloma, Javier; Calsina, Bruna; Currás-Freixes, Maria; Letón, Rocío; Torres-Pérez, Rafael; Richter, Susan; Pita, Guillermo; Herráez, Belén; Cianchetta, Giovanni; et al. (American journal of human genetics, 2019)
Pheochromocytomas and paragangliomas (PPGLs) provide some of the clearest genetic evidence for the critical role of metabolism in the tumorigenesis process. Approximately 40% of PPGLs are caused by driver germline mutations in 16 known susceptibility genes, and approximately half of these genes encode members of the tricarboxylic acid (TCA) cycle. Taking as a starting point the involvement of the TCA cycle in PPGL development, we aimed to identify unreported mutations that occurred in genes involved in this key metabolic pathway and that could explain the phenotypes of additional individuals who lack mutations in known susceptibility genes. To accomplish this, we applied a targeted sequencing of 37 TCA-cycle-related genes to DNA from 104 PPGL-affected individuals with no mutations in the major known predisposing genes. We also performed omics-based analyses, TCA-related metabolite determination, and 13C5-glutamate labeling assays. We identified five germline variants affecting DLST in eight unrelated individuals (∼7%); all except one were diagnosed with multiple PPGLs. A recurrent variant, c.1121G>A (p.Gly374Glu), found in four of the eight individuals triggered accumulation of 2-hydroxyglutarate, both in tumors and in a heterologous cell-based assay designed to functionally evaluate DLST variants. p.Gly374Glu-DLST tumors exhibited loss of heterozygosity, and their methylation and expression profiles are similar to those of EPAS1-mutated PPGLs; this similarity suggests a link between DLST disruption and pseudohypoxia. Moreover, we found positive DLST immunostaining exclusively in tumors carrying TCA-cycle or EPAS1 mutations. In summary, this study reveals DLST as a PPGL-susceptibility gene and further strengthens the relevance of the TCA cycle in PPGL development.